Dissipation of the Proton Electrochemical Potential in Intact Chloroplasts (II. The pH Gradient Monitored by Cytochrome f Reduction Kinetics). - Nishio, J. N. (1993)
The potency of various uncouplers for collapsing the light-induced pH gradient across thylakoid membranes in intact chloroplasts was investigated by time-resolved optical spectroscopy. The thylakoid transmembrane pH gradient ([delta]pH) was monitored indirectly by measuring the rate of cytochrome (Cyt) f reduction following a light flash of sufficient duration to create a sizable [delta]pH. The results show that the rate of Cyt f reduction is controlled in part by the internal pH of the thylakoid inner aqueous space. At pH values from 6.5 to 8.0, the Cyt f reduction rate was maximal, whereas at lower pH values from 6.5 to 5.5 the reduction rate decreased to 25% of the maximal rate. The ability of three uncouplers, nigericin, carbonylcyanide m-chlorophenylhydrazone, and gramicidin, to accelerate the rate of Cyt f reduction was determined for intact chloroplasts isolated from spinach (Spinacia oleracea). The efficacy of the uncouplers for collapsing the [delta]pH was determined using the empirical relationship between the [delta]pH and the Cyt f reduction rate. For intact chloroplasts, nigericin was the most effective uncoupler, followed by carbonylcyanide m-chlorophenylhydrazone, which interacted strongly with bovine serum albumin. Gramicidin D, even at high gramicidin:chlorophyll ratios, did not completely collapse the pH gradient, probably because it partitions in the envelope membranes and does not enter the intact chloroplast.